Pengolahan Slurry Sampah melalui Microbial Fuel Cells di Pasar Giwangan Yogyakarta - Ilham Mufandi; Isti Nur Azizah; Arpan Efendi; Zahrul Mufrodi (CHEMICA: Jurnal Teknik Kimia, 2018)
The vegetable waste is one of the biomass types that it can produce electrical energy.Â  This article focused on electrical production of vegetable waste using microbial fuel cells (MFCS) MFCs is the primary type of the bioelectrochemical system (BECs) that to replaces the biomass to electrical energy spontaneously by activity metabolism of the microorganism. The objectives of this work were to investigate the process of electrical production from Chinese cabbage and the combination of the materials to produce the electrical energy. The experiment was carried out in a laboratory-sall such as mini reactor MFCs, Chinese cabbage as the material of vegetable waste and EM4 as the fermentation. Sample combination was consist of two parts that the first part was used 1 kg Chinese cabbage, 2 liter water and 20 ml EM4. The second part was used 2 kg Chinese cabbage, 1 liter water and 20 ml EM4. The result showed that the electrical voltage in part 1 at 0.362 V and pH at 6 was lower than the electrical voltage in part 2 at 0.724 V and pH at 7. Declining electric energy is influenced by pH as microorganisms living place and the formation process of attached media at the electrode.